Alternativa para el tratamiento de la atrofia severa de maxilar superior: casos clínicos de implantes cigomáticos - Lazarte, Carlos (2020)
Implant-prosthetic rehabilitation of severe atrophic maxilla is a challenge for clinicians. Decision making when patients lack of bone density or quantity is usually difficult. The aim of this study is to report two cases of severe atrophic maxilla treated through zygomatic implants. Two clinical reports using the Branemark methodology are presented, in which surgical alternatives are discussed. One patient had post-surgical pain in the peri orbital area and could be solved immediately. No other surgical complications were observed. Prosthetic alternatives are also discussed. After 12 and 18 months of functional loading, neither surgical nor prosthetic problems occurred. In conclusion, zygomatic implants are a viable, short time, low morbidity treatment in patients with an atrophic maxilla and present success rates similar to conventional implants.